Prophètes et prophétie chez Giuseppe Mazzini - Laura Fournier-Finocchiaro; Jean-Yves Frétigné (Laboratoire Italien)
In this article, the authors intend to provide contextualization of Mazzini’s prophetic speech, in order to highlight its genealogy and originality and to describe thoroughly its argumentation and structure. Laura Fournier-Finocchiaro examines first the role that Mazzini assigns to prophets in Italian and European history, past and present, from Dante, Gioacchino da Fiore and Machiavelli to Félicité de Lamennais and the Italian and Polish poets-prophets of the Risorgimento. In the second part of the article, Jean-Yves Frétigné studies the mazzinian idea of the Third Rome in order to appraise its links with prophecy. Far from being a mere allegory aimed at galvanizing the Italian patriots, Mazzini’s Third Rome takes on the form of a belief which is experienced like a revelation, thus making Mazzini one of the leading representative of a democratic spirituality nourished by Christian principles.